2022
DOI: 10.2147/dddt.s369473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remdesivir on SARS-CoV-2 Clearance in a Real-Life Setting: A Matched-Cohort Study

Abstract: Background Evidence regarding the impact of remdesivir (RDV) on SARS-CoV-2 viral clearance (VC) is scarce. The aim of this study was to compare VC timing in hospitalized COVID-19 patients who did or did not receive RDV. Methods This was a matched-cohort study of patients hospitalized with pneumonia, a SARS-CoV-2-positive nasopharyngeal swab (NPS) at admission, and at least one NPS during follow-up. Patients who received RDV (cases) and those who did not (controls) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…According to these results, regulatory agencies approved this modality of treatment, which soon became extensively employed. Even if limited by low numbers of patients included, emerging real‐life data on 3‐day remdesivir treatment course demonstrated a significant reduction of hospitalization risk, which set closely to risk reduction reported by registration clinical trials and showed also reduction of viral SARS‐CoV‐2 positivity 25–31 . However, most of these experiences ‐had a small sample size and often importantly limited by the lack of a control group 25–31 …”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…According to these results, regulatory agencies approved this modality of treatment, which soon became extensively employed. Even if limited by low numbers of patients included, emerging real‐life data on 3‐day remdesivir treatment course demonstrated a significant reduction of hospitalization risk, which set closely to risk reduction reported by registration clinical trials and showed also reduction of viral SARS‐CoV‐2 positivity 25–31 . However, most of these experiences ‐had a small sample size and often importantly limited by the lack of a control group 25–31 …”
Section: Introductionmentioning
confidence: 63%
“…Even if limited by low numbers of patients included, emerging reallife data on 3-day remdesivir treatment course demonstrated a significant reduction of hospitalization risk, which set closely to risk reduction reported by registration clinical trials and showed also reduction of viral SARS-CoV-2 positivity. [25][26][27][28][29][30][31] However, most of these experiences -had a small sample size and often importantly limited by the lack of a control group. [25][26][27][28][29][30][31] Therefore, in this study we aimed at assessing the real-life effectiveness of a 3-day course of remdesivir, administered in the outpatient's clinic, in a cohort of patients with COVID-19 at high risk of COVID-19 progression in comparison with a cohort of patients who did not receive the antiviral treatment despite being eligible (controls).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective single-center cohort study showed a significantly lower ( p = 0.001) mortality rate when RDV infusion started within 6 days of symptoms, while there was no significant difference when symptom duration exceeded 6 days [ 25 ]. Early administration of a 5-day course of remdesivir (within two days of admission) was associated with a significantly shorter time to clinical improvement, lower viral load [ 26 ] and positive IgG antibodies, reduced length of hospital stay, and lower risk of in-hospital death [ 27 ]. In another retrospective single-center study, the threshold of clinical benefit was set to 9 days from symptom onset for the initiation of RDV when significantly lower all-cause mortality was documented ( p = 0.004) [ 28 ].…”
Section: Remdesivir Outcomesmentioning
confidence: 99%